The Double Failure of the Master and the Slave Highlighted in Selected Works by Chinua Achebe and Amma Darko - Houndjo, Théophile (International Journal of Social and Administrative Sciences, 2018)
Colonization was sealed by the Berlin Conference in 1885 and represents the second main stage in the contact between Africa and Europe after slave trade. The aftermaths of colonization are still noticeable in Africa and will still be in the future. Although many documents, through ages, have dealt with what the relationships between Europe and Africa have usually been some African novelists have also dealt with either the colonization of their continent or its aftermath or both. Among them are Chinua Achebe and Amma Darko. This paper, based on Things Fall Apart and No Longer At Ease by Chinua Achebe, and on Beyond The Horizon by Amma Darko, aims at pointing out the failures of both the colonizer and the colonized. Marxism as a literary theory and the qualitative analysis approach have enabled me to realize that the two novels by Achebe and the one Amma Darko under study depict, in one way or the other, the socio-political and religious situations in most black (African) countries from pre-colonial to the post-independence periods. The study has reached the following conclusions. First both Europeans Africans are responsible for the underdevelopment situation Africa has experienced so far which is a failure. Then the Europeans’ failure to prevent by all costs Africans from immigrating to their continent. Last Africans’ failure to adopt adequate political and economic systems that can help develop their continent, compelling then their fellows to emigrate to Europe, where most of them end in despair and misery.